1996
DOI: 10.1073/pnas.93.26.15405
|View full text |Cite
|
Sign up to set email alerts
|

Muramic lactam in peptidoglycan of Bacillus subtilis spores is required for spore outgrowth but not for spore dehydration or heat resistance

Abstract: Bacterial endospores derive much of their longevity and resistance properties from the relative dehydration of their protoplasts. The spore cortex, a peptidoglycan structure surrounding the protoplasm, maintains, and is postulated to have a role in attaining, protoplast dehydration. A structural modification unique to the spore cortex is the removal of all or part of the peptide side chains from the majority of the muramic acid residues and the conversion of 50% of the muramic acid to muramic lactam. A mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
345
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(363 citation statements)
references
References 31 publications
18
345
0
Order By: Relevance
“…This latter mutation results in a modified spore cortex lacking muramic acid lactam, the recognition determinant for the enzymes that initiate cortex hydrolysis during spore germination (2,8,36,37). Consequently, although cwlD spores will initiate germination in response to nutrients and release DPA rapidly, they cannot progress past stage I of germination, and the core water content of germinated cwlD spores [Ϸ60% of wet weight (7,8)] is only slightly above that of dormant spores of several other Bacillus species (5). As was found with GFP in dormant wild-type spores, GFP in dormant cwlD spores was also essentially immobile ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter mutation results in a modified spore cortex lacking muramic acid lactam, the recognition determinant for the enzymes that initiate cortex hydrolysis during spore germination (2,8,36,37). Consequently, although cwlD spores will initiate germination in response to nutrients and release DPA rapidly, they cannot progress past stage I of germination, and the core water content of germinated cwlD spores [Ϸ60% of wet weight (7,8)] is only slightly above that of dormant spores of several other Bacillus species (5). As was found with GFP in dormant wild-type spores, GFP in dormant cwlD spores was also essentially immobile ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the large peptidoglycan cortex around the spore core is degraded, and removal of this restraint allows the spore core to expand rapidly by uptake of water and thus complete stage II of germination (2,7). This latter event results in a level of core water (75-80% of wet weight) that is similar to that in growing cells (8). As noted above, there is neither metabolism nor enzyme action in the cytoplasm of dormant spores, although there are several enzyme-substrate pairs located in this region of the spore (3).…”
mentioning
confidence: 95%
“…The iosgenic Bacillus subtilis strains used in this work are derivatives of strain 168 and were: PS832, a prototrophic derivative of strain 168; PS3207, cwlD::cam, in which the cwlD gene responsible for production of muramic acid-␦-lactam in the spore cortex (14,26) has been deleted and replaced with a chloramphenicol resistance marker; and PS3328 (27), cotE::tet in which the cotE gene responsible for proper assembly of much of the spore coat as well as outer spore membrane integrity (28) has been deleted and replaced with a tetracycline resistance marker. The fluorescent probes used were pyridinium, 4-…”
Section: Methodsmentioning
confidence: 99%
“…A variety of data indicate that it is the spore's inner membrane that is the major permeability barrier restricting the passage of small molecules into the spore core (3-7), although the lipid composition of the inner membrane exhibits no anomalies that might explain its unusual properties (8)(9)(10)(11)(12). In addition, the dormant spore's inner membrane has the potential to expand significantly, because electron microscopy indicates that the volume this membrane encompasses (the spore core): (i) decreases as much as 2-fold late in sporulation (13); and (ii) increases up to 2-fold in the first minute of spore germination, when the spore's large peptidoglycan cortex is degraded and the germ cell wall expands (13)(14)(15). This increase in core volume during spore germination takes place without new membrane synthesis, because ATP production is not required, and restores relatively normal permeability to the germinated spore's plasma membrane (4,5,16,17).…”
mentioning
confidence: 99%
“…Sekiguchi et al (1995) reported that the germination rate of the cwlD mutant in B. subtilis was less than 3.7 x 10 -8 , but our results were 1.9x 10 -4 and 1.7 x 10 -3 for 168 and NAFM5, respectively. Popham et al (1996) showed that the germination rate of the cwlD mutant in B. subtilis was 5 x 10 -4 (with the respect to the wild type).…”
Section: Analysis Of Nattomentioning
confidence: 99%